Pre-sowing seed treatment and germination behavior of pomegranate (Punica granatum L.) cv Ganesh - Kumar, Sudhir; Nagaich, Divya; Prasad, Rajendra (Indian Journal of Agroforestry, 2020)
Present study was carried out in nursery under 60% shade net house at National Research Centre for Agro forestry, Jhansi during March to June, 2011 to see the effect of pre-sowing treatments of KNO3Â and soaking period on seed germination of pomegranate cv. Ganesh. The experiment comprised of thirteen treatments, four replications with twenty five seeds of each replication under complete randomized block design. The findings revealed that in pomegranate germination started on 10th day after sowing in almost all treatments and lasted for 29 days. Maximum germination percent, fastest germination rate, maximum mean daily germination, highest peak value, more germination value and higher shoot vigor index were recorded in treatment T7 (soaking withÂ KNO3 1% for 12 hours) with ranking first in most of the cases or at parwith the treatment where it is not having first rank.